PELAKSANAAN METODE TASBIH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL QURAN - Rizki Alfajri Zein; Reffa Muhammad Adedyo; Syarnubi (PAI RAFAH, 2023)
The Tasbih Method emphasizes structured repetition and consistency in recitation practice, similar to the use of tasbih in dhikr. This research uses a qualitative method with a literature study approach and interviews to examine theories, concepts, and research results related to the Tasbih Method. Ustadz Rahman explained that the book "Tasbih Method: A Quick Solution to Reading the Al-Qur’an" aims to help Muslims read the Al-Qur’an fluently and quickly without reducing the accuracy of tajweed and makhraj. This book has also been recognized by the Indonesian Ministry of Religious Affairs as one of the methods of learning to read the Qur'an. Learning with the Tasbih Method involves repeating the Qur'anic verses with rhythm and hand movements to help memorize and understand the verses. This technique makes the learning process more interesting and effective, especially for children. Ustadz Rahman also emphasizes the importance of family support in learning the Qur'an, as well as the need for teachers who are experienced in teaching tajweed to improve the quality of learning. The results showed that the Tasbih Method significantly improved learners' ability to read the Qur'an. This method also helps in strengthening memory and deepening the participants' understanding of the Qur'anic verses. With its fun and engaging approach, the Tasbih Method has great potential to be widely applied in Qur'anic education in various Islamic educational institutions.